Ex vivo Validation of Noninvasive Epicardial and Endocardial Repolarization Mapping - van der Waal, Jeanne G.; Meijborg, Veronique M. F.; Belterman, Charly N. W.; Streekstra, Geert J.; Oostendorp, Thom F.; Coronel, Ruben (Frontiers in Physiology, 2021)
Background Detection and localization of electrophysiological substrates currently involves invasive cardiac mapping. Electrocardiographic imaging using the equivalent dipole layer (EDL) method allows non-invasive estimation of endocardial and epicardial activation and repolarization times (RT), but RT-validation is limited to in-silico studies. We aimed to assess the temporal and spatial accuracy of the EDL method in reconstructing the RTs from the surface ECG under physiological circumstances and situations with artificially induced increased repolarization heterogeneity. Methods In four Langendorff perfused pig hearts, we simultaneously recorded unipolar electrograms from plunge needles and pseudo-ECGs from a volume conducting container equipped with 61 electrodes. The RTs were computed from the ECGs during atrial and ventricular pacing and compared to those measured from the local unipolar electrograms. Regional RT prolongation (cooling) or shortening (pinacidil) was achieved by selective perfusion of the LAD-region. Results The difference between the computed and the measured RTs was 19.0±17.8 and 18.6±13.7 ms for atrially and ventricularly paced beats. The region of artificially delayed or shortened repolarization was correctly identified, with minimum/maximum RT roughly in the center of the region in 3 hearts. In one heart, the reconstructed region was shifted by approximately 2.5 cm. The total absolute difference between measured and calculated RTs for all analyzed patterns in selectively perfused hearts (n=5) was 39.6±27.1 ms. Conclusion Non-invasive electrocardiographic repolarization imaging using the EDL method of atrially and ventricularly paced beats allows adequate quantitative reconstruction of regions of altered repolarization.